WATER QUALITY ANALYSIS OF AN URBAN WATERSHED IN THE CERRADO-PANTANAL ECOTONE: CASE STUDY (Editora Impacto Científico, 2025)
This study evaluated the water quality of the Lagoa Comprida Microbasin in Aquidauana, Mato Grosso do Sul. This area represents a low-elevation area that also receives urban stormwater runoff. Six sampling points were selected (outfalls, a downstream point, and the mouth). Parameters such as temperature (T), pH, and electrical conductivity (EC) were measured with a multiparameter probe. Water samples were also collected for laboratory analysis of turbidity (Tur), total phosphorus (Pt), total nitrogen (Nt), thermotolerant coliforms (CT), and Escherichia coli (EC). Despite being classified as a Special Class by the regulations of the State of Mato Grosso do Sul, the research revealed that the water body is degraded. High concentrations of NT and PT, as well as pH and T values, reinforce ideal conditions for eutrophication. Factors such as siltation, asphalt sealing, unobstructed access to the watershed surroundings, and a lack of basic sanitation, especially the lack of a sewage system, significantly contribute to this deterioration. The results show that, in practice, the natural conditions of Lagoa Comprida are not being preserved, requiring urgent action for its recovery.DOI: https://doi.org/10.56238/edimpacto2025.090-013